The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.15171/bi.2018.24
|View full text |Cite|
|
Sign up to set email alerts
|

A cancer vaccine with dendritic cells differentiated with GM-CSF and IFNα and pulsed with a squaric acid treated cell lysate improves T cell priming and tumor growth control in a mouse model

Abstract: Introduction: Ovarian cancer is one of the most lethal gynecologic cancers. Relapses after remission are common, hence novel strategies are urgently needed. Our group has previously developed a vaccination approach based on dendritic cells pulsed with HOCl-oxidized tumor lysates. Here we investigate the improvement of this vaccine strategy using squaric acid treatment of cancer cells during tumor lysate preparation and by differentiating dendritic cells in the presence of GM-CSF and IFNα. Methods: Induction o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 51 publications
(62 reference statements)
0
15
0
Order By: Relevance
“…Therefore, it is extremely important to add adjuvant to enhance the immune effects of vaccines to prolong the immune cycle. The enhanced immune function of GM-CSF has been confirmed in many studies (Dey, Chellappa, & Pathak, 2017;Mookerjee, Graciotti, & Kandalaft, 2018). GM-CSF can stimulate the activation and maturation of DCs, which are the most effective antigen presenting cells in the immune system (Ma, Lee, & Liu, 2017).…”
Section: Discussionmentioning
confidence: 89%
“…Therefore, it is extremely important to add adjuvant to enhance the immune effects of vaccines to prolong the immune cycle. The enhanced immune function of GM-CSF has been confirmed in many studies (Dey, Chellappa, & Pathak, 2017;Mookerjee, Graciotti, & Kandalaft, 2018). GM-CSF can stimulate the activation and maturation of DCs, which are the most effective antigen presenting cells in the immune system (Ma, Lee, & Liu, 2017).…”
Section: Discussionmentioning
confidence: 89%
“…In order to map modifications at the amino acid level induced by HOCl oxidation, we followed an optimized protocol previously used by our group in clinical vaccination studies, by incubating for one hour A375 melanoma tumor cells in the presence of HOCl, followed by six cycles of freeze/thaw to generate the WTL [ 16 , 31 , 32 ]. These studies showed, in fact, that using this WTL preparation as an antigen source efficiently increased tumor antigen uptake by mo-DCs and vaccine-induced tumor protective effects, compared to the not-oxidized control counterpart [ 16 , 31 , 32 ]. We then subjected this lysate (Ox-L) to shotgun proteomic analysis by mass spectrometry (MS).…”
Section: Resultsmentioning
confidence: 99%
“…Vaccines have been developed against a large number of infectious and non-infectious diseases [94]. Early attempts focused on the recombinant urease showed some promising outcomes in animals, nevertheless, some subsequent clinical trials were hampered by a number of certain side effects of mucosal adjuvants [95].…”
Section: Vaccinesmentioning
confidence: 99%